Sinne, samhold og kjendiser Sykdomsskildringer i skandinavisk samtidslitteratur - Nesby, Linda (Scandinavian University Press (Universitetsforlaget), 2021)
Autobiographical and fictional illness narratives meet increased attention these days, both among laymen and women as well as within interdisciplinary research. The genre's popularity can be seen as an offspring of the attention personal experiences have in Scandinavian culture both within publishing, social media, and autobiographical literature. Rage, relations, and celebrities. Contemporary Scandinavian lllness Narratives depicts and discusses how personal illness experiences is a complex phenomenon with regard to the emotions activated when facing illness, the relational diversity, the public discourse aiming at transparence and sharing, as well as commercial and authenticating agendas. The book draws theoretical inspiration from affect theory and Rita Felski's writings on interpretation and literary theory. Rage, relations, and celebrities aims at showing how illness narratives is a flexible literary genre, illustrating some of the challenges but also the potential insights experienced in the light of illness - by patients, relatives, and readers.